Intelektualista w łagrze. Perspektywa Julija Margolina - Lenart, Agnieszka (Studia Rossica Posnaniensia, 2020)
The aim of this article is to attempt to discuss the report of Yuliy Margolin from the Soviet Gulag. A Journey to the Land of Ze-Ka is an original work, written from the perspective of a prisoner, who is mostly an intellectual, a philosopher, an excellent observer and interpreter of European reality. The author of the article tries to prove that for Margolin the superior value in the Gulag is the mind, which wins over emotions and thanks to that allows to preserve dignity and humanity. The analysis of identity, carried out by Margolin, allows us to read his testimony in the context of contemporary identity research in extreme situations, where instead of building up our own self, we are fighting for our moral values. As it turns out, the basic foundation of identity is freedom. The article also undertakes a preliminary analysis of Margolin’s concept of hate as the most destructive force for the human individual and the intellect. The mind, according to Margolin, effectively defends freedom, and hate kills free thought, destroys goodness, and consequently leads to dehumanization. The research allows us to call Margolin a rationally thinking humanist, an intellectual who is against historical fatalism, who constantly analyses current events and human behaviour, without losing faith in the mind and the human individual.